(untitled) (Journal of Global Humanities and Social Sciences, 2025)
This article aims to explore how IoT technology can reshape the traditional movable property financing model and solve its long-standing pain points of "difficult management of goods, difficult financing of funds, and high risks". By reviewing the theoretical foundations of the Internet of Things, supply chain finance, and movable property financing through literature review, and combining typical cases such as JD Technology, Qingdao Free Trade Zone Digital Warehouse, and Tianqi Lithium Battery Recycling, this paper deeply analyzes the business process innovation, risk control optimization, and comprehensive benefit improvement of movable property financing under the integration of "Internet of Things+blockchain" technology. Research has found that IoT technology can greatly improve the accessibility of financing, reduce financing costs, and create new business growth points for financial institutions by achieving real-time, visual, and traceable digital supervision of movable property (inventory, warehouse receipts). Finally, the paper summarizes the challenges faced by the current model and provides prospects for future development directions.